Ste6p Mutants Defective in Exit from the Endoplasmic Reticulum (ER) Reveal Aspects of an ER Quality Control Pathway inSaccharomyces cerevisiae - Diego Loayza; Amy Tam; Walter K. Schmidt; Susan Michaelis (1998)
We are studying the intracellular trafficking of the multispanning membrane protein Ste6p, the a-factor transporter inSaccharomyces cerevisiae and a member of the ATP-binding cassette superfamily of proteins. In the present study, we have used Ste6p as model for studying the process of endoplasmic reticulum (ER) quality control, about which relatively little is known in yeast. We have identified three mutant forms of Ste6p that are aberrantly ER retained, as determined by immunofluorescence and subcellular fractionation. By pulse-chase metabolic labeling, we demonstrate that these mutants define two distinct classes. The single member of Class I, Ste6–166p, is highly unstable. We show that its degradation involves the ubiquitin–proteasome system, as indicated by its in vivo stabilization in certain ubiquitin–proteasome mutants or when cells are treated with the proteasome inhibitor drug MG132. The two Class II mutant proteins, Ste6–13p and Ste6–90p, are hyperstable relative to wild-type Ste6p and accumulate in the ER membrane. This represents the first report of a single protein in yeast for which distinct mutant forms can be channeled to different outcomes by the ER quality control system. We propose that these two classes of ER-retained Ste6p mutants may define distinct checkpoint steps in a linear pathway of ER quality control in yeast. In addition, a screen for high-copy suppressors of the mating defect of one of the ER-retained ste6 mutants has identified a proteasome subunit, Hrd2p/p97, previously implicated in the regulated degradation of wild-type hydroxymethylglutaryl-CoA reductase in the ER membrane.